Neural Processing of Morphology During Reading in Children. (1st March 2022) - Barouch, Bechor; Weiss, Yael; Katzir, Tami; Bitan, Tali
Highlights: Hebrew reading children read bi- and mono-morphemic words during fMRI. Young Hebrew readers are sensitive to the morphological structure of words. Unlike adults, morphological effects in children were in bilateral temporal areas. Unlike adults, morphological effects were only in the transparent (pointed) script. Children may rely more than adults on morpho-semantic aspects during reading. Abstract: The importance of morphological segmentation for reading has been shown in numerous behavioral studies in children and adults. However, little is known about developmental changes in the neural basis of morphological processing. In addition to effects of age and reading skill, morphological processing during reading may be affected by the morphological structure of the language and the transparency of its orthography. Hebrew provides a unique opportunity to study these factors, with its rich morphological structure, and two versions of script that differ in orthographic transparency. Two groups of children (2nd–3rd and 5th–6th graders) were scanned using fMRI while reading aloud Hebrew nouns. Half of the words were composed of roots and templates (bi-morphemic) and half were mono-morphemic. The words were presented at two levels of transparency: with or without diacritics. ROI analyses showed greater activation for mono over bi-morphemic words across groups in the anterior portions of bilateral middle and superior temporal gyri, especially for the transparent script. These results diverge from a previous finding in adults, showing left frontal activation in the non-transparent script with the same stimuli. These results support the early sensitivity of young Hebrew readers to the rich morphological structure of their language but suggest a developmental change in the role of morphological processes during reading. While in adults morpho-phonological segmentation during reading may compensate for orthographic opacity, morphological processes in children may rely more on semantic aspects, and are enhanced by orthographic transparency.